Glycolipids: Linchpins in the Organization and Function of Membrane Microdomains - Hanafusa, Kei; Hotta, Tomomi; Iwabuchi, Kazuhisa (Frontiers in Cell and Developmental Biology, 2020)
Membrane microdomains, also called lipid rafts, are areas on membrane enriched in glycolipids, sphingolipids, and cholesterol. Although membrane microdomains are thought to play key roles in many cellular functions, their structures, properties, and biological functions remain obscure. Cellular membranes contain several types of glycoproteins, glycolipids, and other lipids, including cholesterol, glycerophospholipids, and sphingomyelin. Depending on their physicochemical properties, especially the characteristics of their glycolipids, various microdomains form on these cell membranes, providing structural or functional contextures thought to be essential for biological activities. For example, the plasma membranes of human neutrophils are enriched in lactosylceramide (LacCer) and phosphatidylglucoside (PtdGlc), each of which forms different membrane microdomains with different surrounding molecules and is involved in different functions of neutrophils. Specifically, LacCer forms Lyn-coupled lipid microdomains, which mediate neutrophil chemotaxis, phagocytosis, and superoxide generation, whereas PtdGlc-enriched microdomains mediate neutrophil differentiation and spontaneous apoptosis. However, the mechanisms by which these glycolipids form different nano/meso microdomains and mediate their specialized functions remain incompletely understood. This review describes current understanding of the roles of glycolipids and sphingolipids in their enriched contextures on cellular membranes, including their mechanisms of facilitation and regulation of intracellular signaling. This review also introduces new concepts about the roles of glycolipid and sphingolipid-dependent contextures in immunological functions.